Herb-Induced Liver Injury Related to Reynoutria multiflora (Thunb.) Moldenke: Risk Factors, Molecular and Mechanistic Specifics - Zhai, Xing-Ran; Zou, Zheng-Sheng; Wang, Jia-Bo; Xiao, Xiao-He (Frontiers in Pharmacology, 2021)
Herbal medicine is widely used in Asia as well as the west. Hepatotoxicity is one of the most severe side effects of herbal medicine which is an increasing concern around the world. Reynoutria multiflora (Thunb.) Moldenke (Polygonum multiflorum Thunb., PM) is the most common herb that can cause herb-induced liver injury (HILI). The recent scientific and technological advancements in clinical and basic research are paving the way for a better understanding of the molecular aspects of PM-related HILI (PM-HILI). This review provides an updated overview of the clinical characteristics, predisposing factors, hepatotoxic components, and molecular mechanisms of PM-HILI. It can also aid in a better understanding of HILI and help in further research on the same.